PEMBELAJARAN INOVATIF JIGSAW BERORIENTASI ERGONOMI PADA MATA PELAJARAN BAHASA INGGRIS MENINGKATAN LUARAN PROSES DAN HASIL BELAJAR PESERTA DIDIK KELAS X MA NW GELONDONG - Haqqi, Abdul Hafiz; Sutajaya, I Made; Handari Adiputra, Luh Made Indah Sri; Manuaba, Ida Bagus Adnyana; Sutjana, I Dewa Putu; Swamardika, Ida Bagus Alit (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 4 No 1 (2018): Volume 4 No 1 Juni 2018DO - 10.24843/JEI.2018.v04.i01.p06, 2018)
The learning process involving teachers and students in various activities cause an impact toward learning outcome and learning achievement. Learning outcome in the form of fatigue, boredom and learning achievement relate to the learning condition that applied. One of the innovative learning models was Jigsaw . The learning of innovative jigsaw oriented ergonomic required to create learning condition quality. The aimed of this study was to prove the learning of innovative jigsaw in English subject can increase learning outcome and student’s learning achievement.                This research used nonequivalent randomized pre and posttest control group design , involving 33 sampels which choosed become 16 samples in the control group and 17 samples in the experimental group. The data were collected using boredom questionnaire for boredom, 30 Items of Rating Scale for fatigue and rubric of English speaking language for student’s learning achievement. The normality of data was tested using Shapiro-Wilk test . The normal distribution data were analyzed using t group and the data which was not in normal distribution were analyzed using Mann-Whitney test with significance level 5% (?=0.05).                The result of the research showed that the learning of innovative jigsaw oriented ergonomic in english subject that applied in experimental group increased the learning outcome seen from the fatigue decreased by 23.05%, boredom decreased by 30.25% and student’s learning achivement increased by 27.91%. It could be concluded that the learning of innovative jigsaw oriented ergonomic in English subjects can increase learning outcome and learning achivement. It is suggested that the learning of innovative jigsaw oriented ergonomic not only applied in English subject and on the tenth grade students of Ma NW Gelondong but can be applied to other subjects, grades and schools.